2009
DOI: 10.1007/s11517-009-0509-1
|View full text |Cite
|
Sign up to set email alerts
|

Computer simulation for the optimization of instrumentation strategies in adolescent idiopathic scoliosis

Abstract: Recent studies reveal a large variability of instrumentation strategies in adolescent idiopathic scoliosis (AIS). Determination of the optimal configuration remains controversial. This study aims to develop a method to define the optimal surgical instrumentation strategy using a computer model implemented in a spine surgery simulator (S3). A total of 702 different strategies were simulated on a scoliotic patient using S3. Each configuration was assessed using objective functions that represented different corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 39 publications
1
24
0
Order By: Relevance
“…Indeed, until now, there is no consensus on what possible initial shape of rod could result to a certain sagittal outcome. Decision-making is always based on individual surgeons' preferences and experience [33][34][35]. In this study, although rod deformation occurred, we have found a positive trend between the degree of rod deformation ∆θ and preoperative implant rod angle of curvature θ 1 at the concave side.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…Indeed, until now, there is no consensus on what possible initial shape of rod could result to a certain sagittal outcome. Decision-making is always based on individual surgeons' preferences and experience [33][34][35]. In this study, although rod deformation occurred, we have found a positive trend between the degree of rod deformation ∆θ and preoperative implant rod angle of curvature θ 1 at the concave side.…”
Section: Discussionmentioning
confidence: 49%
“…Optimal scoliosis surgical treatment is not always achieved due to the variability of surgeons' preferences, choice of approach, choice of instrumented level, surgeon experience and different correction objectives [33][34]. Several studies conducted biomechanical modeling to simulate various correction objectives, surgical steps and strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Decision-making on the levels of instrumentation/fixation, types and number of implants, shape and size of implant rod is still dependent on individual surgeon's experience (Desroches et al, 2007;Majdouline et al, 2009). Optimal scoliosis surgical treatment is not achieved due to the variability of surgeons' preferences and different correction objectives.…”
Section: Introductionmentioning
confidence: 99%
“…However, the amount of vertebral rotation and the selection of instrumented vertebrae which would allow the best detorsion may not be predicted. Computer simulation has been advocated to optimize instrumentation strategies [9]. Patient-specific finite element analyses may improve the prediction of correction mechanisms [10].…”
Section: Introductionmentioning
confidence: 99%